Cunning metal core: efficiency/stability dilemma in metallated porphyrin based light-emitting electrochemical cells. Issue 34 (1st July 2016) - Weber, Katharina T.; Karikis, Kostas; Weber, Michael D.; Coto, Pedro B.; Charisiadis, Asterios; Charitaki, Despina; Charalambidis, Georgios; Angaridis, Panagiotis; Coutsolelos, Athanassios G.; Costa, Rubén D.
Abstract : The syntheses, the photophysical/electrochemical characterization, and the first application in LECs of different metallated porphyrins are provided. Abstract : The syntheses, photophysical/electrochemical characterizations of different metallated porphyrins – i.e., Zn 2+, Pt 2+, Pd 2+, and Sn 4+ porphyrins – as well as their first application in light-emitting electrochemical cells are provided. A direct comparison demonstrates that depending on the metallation either efficient (Pt-por) or stable (Zn-por) devices are achieved, demonstrating that the choice of the metal core is a key aspect for future developments.